Ethylene Oxide: Acute Four-Hour and One-Hour Inhalation Toxicity Testing in Rats - William M. Snellings; Donald J. Nachreiner; Lynn H. Pottenger (Journal of Toxicology)
Ethylene oxide was tested on groups of rats for either 4-hour or 1-hour inhalation exposure, followed by 14 days of observation. Groups of five Sprague-Dawley rats/sex were exposed, and clinical signs and mortality were recorded. Clinical signs noted included irregular breathing, absence of certain reflexes, and tremors. Rats that died had moderate to severe pulmonary congestion. The calculated LC50 values, reported as ppm by volume (with 95% confidence limits), were as follows. 4-hour LC50 values were 1972 (1887 to 2061) ppm for males; 1537 (1391 to 1698) ppm for females; 1741 (1655 to 1831) ppm for the combined sexes. The 1-hour LC50 values were 5748 (5276 to 6262) ppm for males; 4439 (4034 to 4884) ppm for females; 5029 (4634 to 5459) ppm for the combined sexes.